2023
DOI: 10.1111/pce.14635
|View full text |Cite
|
Sign up to set email alerts
|

Rapid drought‐recovery of gas exchange in Caragana species adapted to low mean annual precipitation

Abstract: While variation in mean annual precipitation (MAP) of the native habitat of a species has been shown to determine the ability of a species to resist a hydraulic decrease during drought, it remains unknown whether these variations in MAP also influence the ability of a species to recover and survive drought. Leaf hydraulic and gas exchange recovery following drought and the underlying mechanisms of these responses in six Caragana species from habitats along a large precipitation gradient were investigated durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It has been observed that Caragana plants exhibit distinctive distribution patterns, reflecting the evolution of species-specific characteristics in morphology, physiology, and biochemistry [18]. This makes them good candidates for conducting research on plant adaptability [17,[19][20][21]. For instance, C. versicolor is distributed in southern Sichuan, Xizang, and Qinghai, while C. polourensis is observed on the northern slope of Kunlun Mountain in Xinjiang and the northern slope of Qilian Mountain in Gansu.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that Caragana plants exhibit distinctive distribution patterns, reflecting the evolution of species-specific characteristics in morphology, physiology, and biochemistry [18]. This makes them good candidates for conducting research on plant adaptability [17,[19][20][21]. For instance, C. versicolor is distributed in southern Sichuan, Xizang, and Qinghai, while C. polourensis is observed on the northern slope of Kunlun Mountain in Xinjiang and the northern slope of Qilian Mountain in Gansu.…”
Section: Introductionmentioning
confidence: 99%
“…C. brachypoda predominantly scatters across piedmont plains, low slopes, and stabilized sandy lands in the semi-desert regions of Inner Mongolia [22]. So far, extensive research has delved into understanding the adaptive strategies of Caragana plants, spanning various domains, including morphological anatomy [19][20][21], geographical distribution [22,23], physiological ecology [22,[24][25][26][27], photosynthetic characteristics [22,[24][25][26][27], phylogenetic analysis [26,27], and population genetics [28][29][30][31][32]. With the advent of advanced gene sequencing technologies, new frontiers have been opened in unraveling the molecular mechanisms governing stress resistance and adaptive evolution within the genus.…”
Section: Introductionmentioning
confidence: 99%